Business Pivoting Strategy in the Mining Industry (Case Study: PT Membara Bersama Abadi, East Kalimantan, Indonesia) - Edward Darmawan; Uke Siahaan; Sylviana Maya (Jurnal Pendidikan Indonesia, 2025)
PT Membara Bersama Abadi (MBA), a coal mining company in East Kalimantan, Indonesia, is facing a critical business challenge due to the impending expiration of its mining license in 2029 and increasing pressure from global energy transition trends. The company risks significant revenue loss unless it finds a sustainable business model beyond coal. This research aims to evaluate the financial feasibility and strategic viability of converting MBA’s existing coal hauling road into a commercial logistics corridor. The study employs a quantitative approach, analyzing project cash flows, Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Weighted Average Cost of Capital (WACC) using different financing models. The results indicate strong financial performance with a positive NPV ranging from IDR 37.1 to 46.2 billion and IRR exceeding 40%, ensuring payback within 1–2 years. Sensitivity analysis reveals volume risk and regulatory delays as the main threats. The study concludes that infrastructure monetization is a viable strategic pivot for PT MBA, offering long-term financial stability while aligning with Indonesia’s sustainable development goals. The findings provide a model for similar firms navigating post-mining economic uncertainty.